4-Chloro-6-methyl-N-(4-methylphenyl)quinolin-2-amine - Vennila, K. N. (International Union of Crystallography, 2011)
In the title compound C17H15ClN2, the dihedral angle between the quinoline ring system and the phenyl ring is 50.18 (6)°. In the crystal, molecules are linked into chains running along the c axis by N—H⋯N hydrogen bonds.